Reutilisation of coal gangue and fly ash as underground backfill materials for surface subsidence control. (1st May 2020) - Li, Meng; Zhang, Jixiong; Li, Ailing; Zhou, Nan
Abstract: To address the environmental problems caused by solid waste while promoting the sustainable development of mines, gangue and fly ash can be used as underground backfill materials to achieve the comprehensive utilisation of solid waste mining resources. We measured the compressive deformation characteristics of samples with different ratios of gangue to fly ash and analysed their stress-strain relationship and associated changes in their porosities using a YAS-5000 servo testing machine and a homemade compression apparatus. Moreover, we revealed the mechanisms of deformation resistance of gangue and fly ash from both a macro and meso perspective and determined that the optimal ratio of gangue to fly ash is 0.35. In addition, taking the backfill face in Coal Mine as an example, mixed materials of gangue and fly ash at a ratio of 1:0.35 were backfilled into a goaf. After mining of the working face, the surface only sank by 170 mm approximately. This method not only effectively disposes of solid wastes, i.e., gangue and fly ash, on a large scale but also controls surface subsidence to protect adjacent buildings and structures. Therefore, the coordinated development of coal resource mining and environmental protection are realised.